A research coding method to evaluate medical clinicians conduct of behavioral health care in patients with unexplained symptoms. Issue 4 (April 2018) - Grayson-Sneed, Katelyn A.; Smith, Robert C.
Highlights: Efficient, reliable coding checklist. Non-professionals can be trained to use it. Based on behavioral care method for medical clinicians. Based on evidence-based patient-centered method. Based on evidence-based behavioral treatment model. Abstract: Objective: Develop a reliable coding method of a Behavioral Health Treatment Model for patients with Medically Unexplained Symptoms (BHTM-MUS). Methods: Two undergraduates trained for 30 h coded videotaped interviews from 161 resident-simulated patient (SP) interactions. Trained on 45 videotapes, coders coded 33 (20%) of 161 study set tapes for the BHTM-MUS. Guetzkow's U, Cohen's Kappa, and percent of agreement were used to measure coders' reliability in unitizing and coding residents' skills for eliciting: education and informing (4 yes/no items), motivating (2), treatment statements (5), commitment and goals (2), negotiates plan (8), non-emotion patient-centered skills (4), and patient-centered emotional skills (8). Results: 60 items were dichotomized a priori from analysis of the BHTM-MUS and were reduced to 33 during training. Guetzkow's U ranged from .00 to .082. Kappa ranged from 0.76 to 0.97 for the 7 variables and 33 individual items. The overall kappa was 0.87, and percent of agreement was 95.7%. Percent of agreement by item ranged from 85 to 100%. Conclusions: A highly reliable coding method is recommended to evaluate medical clinicians' behavioral care skills in patients with unexplained symptoms. Practice implications: A way to rate behavioral care in patients with unexplained symptoms